Unraveling how multivalency triggers shape deformation of sub-100 nm lipid vesicles - Park, Hyeonjin (2022)
Multivalent ligand-receptor interactions are critical to the function of membrane-enveloped biological and biomimetic nanoparticles, yet resulting nanoparticle shape changes are rarely investigated. Using the localized surface plasmon resonance (LSPR) sensing technique, we tracked the attachment of biotinylated, sub-100 nm lipid vesicles to a streptavidin-functionalized supported lipid bilayer (SLB) and developed an analytical model to extract quantitative details about the vesicle-SLB contact region. The experimental results were supported by theoretical analyses of biotin-streptavidin complex formation and corresponding structural and energetic aspects of vesicle deformation. Our findings reveal how varying the surface densities of streptavidin receptors in the SLB and biotin ligands in the vesicles affects the extent of nanometer-scale vesicle deformation. We also identify conditions, i.e., a critical ligand density, at which appreciable vesicle deformation began, which provides insight into how the membrane bending energy partially counterposes the multivalent binding interaction energy. These findings are generalizable to various multivalent ligand-receptor systems.